2021
DOI: 10.1155/2021/8816055
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Balanced T Helper 9 Cells and Regulatory T Cells in Allergic Airway Inflammation and Tumor Immunity

Abstract: CD4+T helper (Th) cells are important mediators of immune responses in asthma and cancer. When counteracted by different classes of pathogens, naïve CD4+T cells undergo programmed differentiation into distinct types of Th cells. Th cells orchestrate antigen-specific immune responses upon their clonal T-cell receptor (TCR) interaction with the appropriate peptide antigen presented on MHC class II molecules expressed by antigen-presenting cells (APCs). T helper 9 (Th9) cells and regulatory T (Treg) cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 217 publications
(329 reference statements)
0
3
0
Order By: Relevance
“…The MHCs, HLA-DOA, HLA-DPA1, and HLA-DPB1, positively associated with LOXL3 all belongs to MHC Class II molecules (104). MHC class II molecules were found to be expressed by antigen-presenting cells, including antigenpresenting cancer-associated fibroblasts (apCAFs) (105,106). Therefore, these positive association of the MHC Class II molecules might be indirect evidence of apCAFs in HCC, and drugs targeted on these apCAFs might have potential therapeutic values and future studies are needed for further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…The MHCs, HLA-DOA, HLA-DPA1, and HLA-DPB1, positively associated with LOXL3 all belongs to MHC Class II molecules (104). MHC class II molecules were found to be expressed by antigen-presenting cells, including antigenpresenting cancer-associated fibroblasts (apCAFs) (105,106). Therefore, these positive association of the MHC Class II molecules might be indirect evidence of apCAFs in HCC, and drugs targeted on these apCAFs might have potential therapeutic values and future studies are needed for further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, IL-9 has been shown to promote Th17 differentiation and production of IL-17 and IL-6 [103]; in contrast, it has also been shown that IL-9 enhances the suppressive function of Treg [104]. Asthma patients have increased numbers of Th9 cells in peripheral blood mononuclear cells (PBMCs) and increased IL-9 levels in both serum and bronchoalveolar lavage fluid (BALF) [105][106][107][108][109]. Th9 cells and IL-9 promote accumulation and activation of T cells, ILC2s, mast cells, and eosinophils and increase levels of IL-5, IL-13, and IgE in animal asthma models [110].…”
Section: Il-9 Was the Only Cytokine Presenting Significantly Higher L...mentioning
confidence: 99%
“…Moreover, Th9 cells employ multiple mechanisms to orchestrate allergic inflammation, and particularly, their interaction with diverse cell types including mast cells, ILCs, and DCs, to promote coordinated regulation of allergic airway inflammation (31,32). Other than secretion of their signature cytokine IL-9, Th9 cells from mice and humans also secret other cytokines such as IL-10, IL-17, IL-21, and IL-22, to facilitate immune responses in the setting of allergic asthma (33,34). Furthermore, studies on atopic dermatitis demonstrated feasible evidence supporting that the expansion of Th2/Tc2 and Th22/Tc22 may also exert an important role in allergic inflammation (14,35).…”
Section: The Immunological Characteristics Underlying Allergic Asthmamentioning
confidence: 99%